A caged E3 ligase ligand for PROTAC-mediated protein degradation with light - Kounde,C; Shchepinova,M; Saunders,C; Muelbaier,M; Rackham,M; Harling,J; Tate,E (Chemical Communications, 2020)
With the intent of achieving greater spatiotemporal control of PROTAC-induced protein degradation, a light-activated degrader was designed by photocaging an essential E3 ligase binding motif in a BRD4 targeting PROTAC. Proteolysis was triggered only after a short irradiation time, the kinetics of which could be monitored by live-cell video microscopy.